Estudo piloto: avaliação da associação entre polimorfismos genéticos nos genes da proteína transportadora de serotonina (5HTT) e no gene da catecolamina metil transferase (COMT) com a perda de implantes dentários - Chaves, Thais Mariana Neves (2019)
The loss of teeth due to oral diseases or traumatisms decisively affect oral physiology, facial harmony, personality and social behavior of individuals, compromising their quality of life. One solution is the replacement of missing dental elements through dental implants. Although it is a treatment with a lot of technology and study involved, sometimes with unfavorable prognoses can occur. Regarding genetics, simple modifications of the DNA, known as polymorphisms, that have been pointed out as factors protect or increase the risk of an individual to the development of a certain systemic condition. The aim of this research was to investigate two specific 5HTT and COMT genes in the influence for implant failures and also analysis of the association of polymorphisms rs3813034 and rs1042173 on the 5HTT gene and polymorphism rs4818 and rs174675 on the COMT gene with the flaws. Participants attended the course of specialization in implant dentistry at the University Positivo-Curitiba PR. Initially a single evaluator performed the clinical examination and the data collection of the patients. At this moment, the collections of cells for genetic study were carried out to correlate genetic polymorphisms associated to the loss of the implants. The data were cataloged and submitted to descriptive and inferential statistical analysis using SPSS 20.0 (SPSS, Chicago, IL, USA) and STATA (Stata Corporation, college station, Tex, US). Results showed that the dominant C allele was more present in the group that was unaffected by loss of dental implant (p = 0.01) and suggests to play a protective role against the loss of implants. Other alleles of the polymorphisms tested in either the model dominant and recessive, did not appear to be associated with such loss. It was possible to conclude that there was an association between the rs174675 polymorphism in the catecholamine methyltransferase (COMT) gene and the loss of dental implants. In this same polymorphism, it is suggested that the C allele plays a protective role against the loss of dental implants.